Deep inspiration breath hold versus free breathing in postoperative radiotherapy strategy for patients with left-sided breast cancer treated with volumetric modulated arc therapy: A meta-analysis and systematic review - Pin-Yi Chiang; Pin-Jui Huang; Chao-Hsiung Hung; Ching-Po Lin; Chih-Chia Chang (PLoS ONE, 2026)
This meta-analysis aimed to determine the effect of deep inspiration breath hold (DIBH) compared with free breathing (FB) on dose to the organs at risk (OARs), such as the heart, left anterior descending (LAD) coronary artery, lungs, and contralateral breast, in patients with left-sided breast cancer treated with volumetric modulated arc therapy (VMAT). PubMed, EMBASE, and Cochrane Library electronic databases were searched for studies until March 21, 2024. Cochrane RevMan version 5.4 statistical software was used to analyze 11 eligible studies. Standard mean difference (SMD), with 95% confidence interval for OAR dose reductions, was calculated. DIBH considerably resulted in lower mean doses (Dmean) to the heart (SMD =  −1.40 Gy), LAD (SMD = −1.65 Gy), ipsilateral lung (SMD = −0.57 Gy), contralateral lung (SMD = −0.46 Gy), and contralateral breast (SMD = −0.20 Gy). If VMAT was delivered with an arc of >180 O , the heart Dmean reduction was even more pronounced. Subgroup analysis revealed that DIBH efficiently reduced heart Dmean, especially in patients with tumor bed boost without nodal irradiation. DIBH was effective in reducing dose to OARs in patients treated with VMAT in all subgroups, i.e., breast only, with/without tumor bed boost, and with/without nodal irradiation. Furthermore, the use of DIBH is strongly recommended for patients undergoing VMAT with a tumor bed boost or without nodal irradiation, as it is more effective in reducing heart Dmean than FB.